Pengaruh Relationship Marketing, Customer Value, Dan Service Quality Terhadap Customer Loyalty (Studi pada PT. Gadai Terang Abadi Mulia Unit Bangkalan) - Duwi Putri Lestari; Nurhidayah Nurhidayah; Ita Athia (UNIVERSITAS ISLAM MALANG, 2022)
AbstractA goal of this research is 1) Knowing the impact of relationship marketing on customer loyalty PT. Gadai Terang Abadi Mulia Unit Bangkalan. 2) Knowing the impact of customer value on customer loyalty PT. Gadai Terang Abadi Mulia Unit Bangkalan. 3) Knowing the impact of service quality on customer loyalty PT. Gadai Terang Abadi Mulia Unit Bangkalan. The study describes the kind of research explanatory research with a quantitative approach. The source of data used in this study is primary and secondary data. Sampling techniques and populations using non sampling techniques. The analysis used in this research is the instrument test, classic assumption, regresi linier berganda, Uji t, and coefficient determination (R2). The result of the study show 1) Relationship marketing has an impact on customer loyalty PT. Gadai Terang Abadi Mulia Unit Bangkalan. 2) Customer loyalty has an impact on customer loyalty PT. Gadai Terang Abadi Mulia Unit Bangkalan. 3) Service quality has an impact on customer loyalty PT. Gadai Terang Abadi Mulia Unit Bangkalan. Keywords: Customer Loyalty, Relationship Marketing, Customer Value andService Quality